Performance of postural balance in children and adolescents living with and without HIV - Medeiros, Rafaela Catherine da Silva Cunha de; Silva, Racquel Guimarães da; Medeiros, Radames Maciel Vitor; Goes, Carlos Jean Damasceno de; Medeiros, Jason Azevedo de; Santos, Isis Kelly dos; Wilde, Phelipe; Barela, José Angelo [UNESP]; Cabral, Breno Guilherme de Araújo Tinoco; Dantas, Paulo Moreira Silva (Elsevier, 2022)
Research question: The present study aimed to compare the postural control of children and adolescents with and without Human Immunodeficiency Virus (HIV). Methods: A total of 32 children and adolescents (18 with HIV and 14 without) of both sexes, aged 6–18 years, were included in the present study. Participants in the HIV + group were infected through vertical transmission and received antiretroviral therapy. Participants maintained an erect, bipedal posture in the following conditions: with vision, without vision, and on a foam base. Results: Concerning the evaluation of time variables, higher values ​​were observed in the HIV + group for mean anterior-posterior (AP) velocity, mean medial-lateral (ML) velocity, AP perimeter (p = 0.001), and ML perimeter (p = 0.001). Concerning the evaluation of conditions, a difference was observed in the mean AP mean sway amplitude (MSA) (p = 0.039), as the AP MSA was lower with vision than without vision or with foam. Concerning the evaluation of spectral domain variables, higher values ​​were observed in the HIV+ group for the predominant ML frequency (p = 0.04) and mean AP (p = 0.001) and ML frequencies (p = 0.001). Regarding the evaluation of conditions, a difference was found only in the predominant AP frequency (p = 0.001). Higher values ​​were found in the closed eye condition than in with foam (Δ = +103 %). Conclusion: The results of the present study indicated that children and adolescents living with HIV have poorer postural control performance than those without HIV.
Keywords: Adolescence; Childhood; HIV; Postural balance